Inheritance of the VATER/VACTERL association - Bartels, Enrika; Jenetzky, Ekkehart; Solomon, Benjamin; Ludwig, Michael; Schmiedeke, Eberhard; Grasshoff-Derr, Sabine; Schmidt, Dominik; Märzheuser, Stefanie; Hosie, Stuart; Weih, Sandra; Holland-Cunz, Stefan; Palta, Markus; et al. (Pediatric surgery international, 2012)
VATER/VACTERL association refers to the non-random co-occurrence of the following component features: vertebral defects, anal atresia, cardiac malformations, tracheoesophageal atresia, renal abnormalities, and limb defects. Recently, Solomon et al. (Hum Genet 127:731-733, 2010) observed an increased prevalence of component features among first-degree relatives of VATER/VACTERL patients suggesting that in some patients, the disorder may be inherited. To replicate these findings, we investigated 87 VATER/VACTERL patients with the presence of a minimum of three component features and their first-degree relatives (n = 271). No increase in the overall prevalence of component features was observed in first-degree relatives compared to the general population (χ² = 2.68, p = 0.10). Separate analysis for the prevalence of single component features showed a higher prevalence of tracheoesophageal fistula/atresia among first-degree relatives compared to the general population (OR 17.65, 95 % CI 2.47-126.05). However, this was based on occurrence in one family only. Our findings suggest that although familial occurrence renders a genetic contribution likely, the overall risk of recurrence among the first-degree relatives of patients with VATER/VACTERL association is probably very low. Since the patients in the present study were young and no offspring could be studied, estimation of the role of de novo mutations in the development of VATER/VACTERL was not possible.